Assessing participation in a community-based health planning and services programme in Ghana - Baatiema, Leonard (BioMed Central, 2013)
BACKGROUND: Community participation is increasingly seen as a pre-requisite for successful health service uptake. It is notoriously difficult to assess participation and little has been done to advance tools for the assessment of community participation. In this paper we illustrate an approach that combines a ‘social psychology of participation’ (theory) with ‘spider-grams’ (method) to assess participation and apply it to a Community-based Health Planning and Services (CHPS) programme in rural Ghana. METHODS: We draw on data from 17 individual in-depth interviews, two focus group discussions and a community conversation with a mix of service users, providers and community health committee members. It was during the community conversation that stakeholders collectively evaluated community participation in the CHPS programme and drew up a spider-gram. RESULTS: Thematic analysis of our data shows that participation was sustained through the recognition and use of community resources, CHPS integration with pre-existing community structures, and alignment of CHPS services with community interests. However, male dominance and didactic community leadership and management styles undermined real opportunities for broad-based community empowerment, particularly of women, young people and marginalised men. CONCLUSION: We conclude that combining the ‘spider-gram’ tool and the ‘social psychology of participation’ framework provide health professionals with a useful starting point for assessing community participation and developing recommendations for more participatory and empowering health care programmes.